Printmaking at the Dakawa Art and Craft Project : the impact of ANC cultural policy and Swedish practical implementation on two printmakers trained during South Africa's transformation years - Baillie, Giselle Katherine (Rhodes University, Faculty of Humanities, Department of Fine Art, 1999)
In 1998, the national Department of Arts, Culture, Science and Technology published a document aimed at the growth of culture industries in South Africa (DACST, "Creative South Africa", July 1998). Focussing on aspects of economic growth which this development could generate for South Africa, it nonetheless points to issues of cultural understanding which need to be addressed. Projects aimed at the development of arts and culture in South Africa have followed troubled paths. While projects aimed at establishing discourse for this development have succeeded on many levels, the imperatives of showcasing, rather than implementing cultural concepts appropriate to South African contexts, have tended to dominate. When the Dakawa Art and Craft Project was established by the ANC, in 1992, in Grahamstown, as the locus for the deve! opment of an arts and culture discourse in the liberated South Africa, all seemed set for success. Yet, less than four years after opening, the Project was closed. While speculatory reasons for closure tended to focus on financial and administrative problems, the basis for this closure had its roots in problems of cultural understanding manifesting themselves at the Project. These reflected a lack of cultural understanding on the part of the ANC and SIDA, the Swedish administrators sent to the Project, and the lack of clear cultural guidelines on the part of the trainees to the Project itself. These reasons for the Project's failure are integral to an understanding of arts add culture development and needs in South Africa today. As other projects, aimed at the same issues of development grow, an understanding of the history of the Project's failure is essential, for it poses questions still in need of answers. Part One examines the historical significance of the Dakawa Art and Craft Project between 1982 and 1994, recording the reasons for its establishment, the path of implementation it followed, and the cultural misunderstandings it posed to development. Part Two examines the cultural context of the trainees to the Project, followed by an account of the printmaking teaching practice, and the effects of cultural concepts on two printmakers trained during the Project's initial establishment, at the time of South Africa's political transformation.
Keywords: Prints -- Technique; Dakawa art and craft project; Printmakers -- South Africa -- Grahamstown; Prints -- Technique -- Study and teaching